2020
DOI: 10.1093/scan/nsaa166
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the average brain: individual differences in social brain development are associated with friendship quality

Abstract: We tested whether adolescents differ from each other in the structural development of the social brain and whether individual differences in social brain development predicted variability in friendship quality development. Adolescents (N = 299, Mage T1 = 13.98 years) were followed across three biannual waves. We analysed self-reported friendship quality with the best friend at T1 and T3, and bilateral measures of surface area and cortical thickness of the medial prefrontal cortex (mPFC), posterior superior tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 47 publications
2
22
0
Order By: Relevance
“…A recent study on brain structure using the same sample as described previously (Braams et al, 2014;Schreuders et al, 2021) also supports the role of mentalizing processes in friendships (Becht et al, 2021). In the study, of 8-to 25-year-olds, researchers examined the link between friendship quality and structure of the social brain network (i.e., the brain regions involved in social cognition).…”
Section: F R I En D Sh I P S a N D M En Ta Li Zi Ngmentioning
confidence: 67%
“…A recent study on brain structure using the same sample as described previously (Braams et al, 2014;Schreuders et al, 2021) also supports the role of mentalizing processes in friendships (Becht et al, 2021). In the study, of 8-to 25-year-olds, researchers examined the link between friendship quality and structure of the social brain network (i.e., the brain regions involved in social cognition).…”
Section: F R I En D Sh I P S a N D M En Ta Li Zi Ngmentioning
confidence: 67%
“…Youth that is more inclined to use social media might have different baseline cortical thickness due to, for example, an increased sensitivity to social cues in general, and these differences might increase or decrease the individual differences across development. There is some support for the latter, as a recent study using the same sample showed that better friendship quality was also related to higher baseline levels of MPFC cortical thickness ( Becht et al, 2021 ). Better friendship quality and social media use might both be driven by individual differences in social competence and associated structural brain anatomy.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have shown a decrease of surface area and cortical thickness in specifically these regions across adolescence ( Mills et al, 2014a , Mills et al, 2014b , Tamnes et al, 2017 , Wierenga et al, 2014 ). Moreover, these regions have been related to social media use specifically (MPFC, LPFC, Wilmer et al, 2019 ) or social relations in general (TPJ, pSTS, ( Becht et al, 2021 , Blakemore, 2008 ). We therefore used these four regions as a starting point to unravel if – and how - individual differences in social media use were associated to individual differences in structural brain development.…”
Section: Introductionmentioning
confidence: 99%
“…Possibly, mPFC is functionally connected to separable networks, such as the genetically influenced DMN (Glahn et al, 2010 ) and social salience network (Achterberg, Van Duijvenvoorde, van IJzendoorn, Bakermans‐Kranenburg, & Crone, 2020 ), depending on the domain that is targeted. Prior studies that examined structural development of the mPFC showed strong influences of genetic estimates on mPFC cortical thickness (van der Meulen et al, 2020 ), whereas others showed that cortical thickness development is influenced by friendship experiences (Becht et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%